Air travel taxes in Airline industry: a systematic literature review - Nur Aaina Aqilah Jamaluddin,; Mohd Rizal Pali,; Azwanis Azemi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Air travel taxes have been practised in numerous nations for decades, but are rarely mentioned in existing literature, although some researchers have explored indirect taxes from the airline industry’s standpoint. This research is attempting to fill this gap in the literature using a systematic literature review to better understand airline travel taxes. In the absence of systematic air transport and taxation studies, this systematic literature study was employed to achieve a goal. The goal was to consolidate aviation tax information from countries that are implementing these taxes. The primary objective was to consolidate the knowledge and perspective of different scholars on air travel taxes to understand the purposes and types of taxes in the airline industry. The need for this research was to significantly influence social acceptance and to enhance the knowledge and understanding of the public regarding the airline industry and its related taxes. This study also strived to clarify issues of air passenger taxes by reviewing 18 out of 1,010 articles published from 2007 to 2019 that fit the inclusion criteria from online databases namely Web of Sciences, Scopus, Wiley, EBSCOhost, and Taylor & Francis. This study has identified two considerations in imposing air travel taxes: economic growth and sustainable development. In addition, five sub-themes were found, namely, revenue-raising, tourism strategies, fundraising initiatives, environmental, and pandemic. The findings explained the importance of air travel taxes and the purpose of tax imposition based on the selected articles. Nonetheless, further studies are needed by investigating air travel taxes studies in Asia Pacific regions.